Association of Replicating Bacteriophage T7 DNA with Bacterial Membranes - Pacumbaba, Rodulfo P. (1973)
Infection of Escherichia coli with bacteriophage T7 leads to the formation of an association between host membranes and newly synthesized T7 DNA. Evidence for this conclusion is suggested by the findings that replicating T7 DNA cosediments with host membranes in sucrose and cesium chloride density gradients. Furthermore, the sedimentation rate of T7 DNA is dependent on the integrity of membrane structure. Finally, an association between DNA and membranes can be demonstrated by electron microscope studies.